Perception and Assertiveness Practices in the Ewuh Pekewuh Concept: an Indigenous Psychology Approach in Yogyakarta Society - Dwi Indah Ratnawati (International Journal Labs, 2025)
The concept of ewuh pekewuh in Javanese culture can be learned from the aspect of Indigenous Psychology. It can affect the way individuals openly express thoughts, feelings, and desires, which is at the core of assertive behavior. This study is important to understand how local cultural values shape communication patterns, as well as to identify how the people of Yogyakarta interpret and practice assertive communication in the concept and frame of cultural values of ewuh pekewuh, a social norm that reflects reluctance, respect, and reluctance to offend others. Using an indigenous psychology approach, the focus of this study explores local understandings of assertiveness, which have been constructed more from a Western perspective. The method used is participatory and contextual reflective observation, by relating and trying to bridge modern communication psychology with local wisdom, as well as uncovering the psychological reality of Javanese society which has been underrepresented in global communication theory. The results of this paper are expected to make theoretical and practical contributions in understanding the dynamics of assertive communication based on local culture, as well as become the basis for the development of communication interventions that are more contextual and sensitive to the cultural values of Indonesian society.